2008
DOI: 10.1007/s12010-008-8138-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Operating Parameters on the Biodelignification of Eucalyptus globulus Kraft Pulps in a Laccase–Violuric Acid System

Abstract: The potential of a laccase mediator system on the delignification of Eucalyptus globulus kraft pulp was investigated under diverse operating conditions. A series of enzymatic treatments were performed to determine how biodelignification is influenced by pulp consistency, oxygen pressure, reaction time, dose of laccase, and dose of mediator. The mediator used was violuric acid. The results revealed that the extent of biodelignification remains practically constant between 1% and 2.5% of pulp consistency then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Although no additional lignin was removed during the second interval, brightness increased by effect of a modification in previously oxidized lignin or the system removing other coloured compounds containing carbonyl or carboxyl groups [25,26]. A similar effect of the reaction time was recently observed elsewhere [27].…”
Section: Lowsupporting
confidence: 61%
“…Although no additional lignin was removed during the second interval, brightness increased by effect of a modification in previously oxidized lignin or the system removing other coloured compounds containing carbonyl or carboxyl groups [25,26]. A similar effect of the reaction time was recently observed elsewhere [27].…”
Section: Lowsupporting
confidence: 61%
“…The differences in delignification efficiency between LairE and LoE were less significant than those of LsE with LairE and LoE at long treatment times; however, delignification was slightly more marked with LoE. Oudia et al (2008) reported delignification increased from 38.9 % with air 6 to 47.9 % with oxygen at 11 bar on eucalyptus kraft pulp and there was a significantly different effect of oxygen under pressure from the atmospheric air environment until they reached 5 bar.…”
Section: Variation Of the Kappa Numbermentioning
confidence: 82%
“…Previous studies on the influence of the treatment time with a LMS on the extent of pulp delignification on reactions with lignin model compounds or eucalyptus kraft pulp revealed that the process involves two distinct stages [10,11,12]. In the initial stage, the pulp is rapidly delignified to a limiting kappa number similarly as in ozone-based treatments [13,14]; in the final stage, delignification is slow but the oxygen uptake continues to be high, which suggests the presence of active chemical species in the system not reacting with residual lignin, but rather interacting with lignin fragments via side reactions [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 PcL, which features a high redox potential and thermal stability, and was previously tested for bleaching different types of pulp was used in combination with syringaldehyde or SA (720 mV), 30 a natural mediator with the potential for delignifying flax pulp, and violuric acid or VA (719 mV), 30 which is one of the most efficient synthetic mediators but had never previously been applied to flax pulp. 14,28 MtL (Novozym  51 003) is a robust, thermostable commercial laccase that acts efficiently in the presence of the natural mediator methyl syringate (705 mV). 30 Six different bleaching sequences were investigated, namely Control PcL and Control MtL, two control sequences where the L stage was carried out with laccase from P. cinnabarinus and M. thermophila, respectively, in the absence of mediator; PcL + SA and PcL + VA, where L was performed with the combination of PcL and the mediator SA and VA, respectively; Xyl + (PcL + VA), which included a xylanase pretreatment and an L stage with PcL and VA; and MtL + MS, which included an L stage with MtL in the presence of MS as mediator.…”
Section: Resultsmentioning
confidence: 99%